Encoding and reinstatement of threat: Recognition potentials - Weymar, Mathias (2013)
On a recognition test, stimuli originally encoded in the context of shock threat show an enhanced late parietal positivity during later recognition compared to stimuli encoded during safety, particularly for emotionally arousing stimuli. The present study investigated whether this ERP old/new effect is further influenced when a threat context is reinstated during the recognition test. ERPs were measured in a yes-no recognition test for words rated high or low in emotional arousal that were encoded and recognized in the context of cues that signaled threat of shock or safety. Correct recognition of words encoded under threat, irrespective of reinstatement, was associated with an enhanced old-new ERP difference (500–700 ms; centro-parietal), and this difference was only reliable for emotionally arousing words. Taken together, the data suggest that information processed in a stressful context are associated with better recollection on later recognition, an effect that was not modulated by reinstating the stressful context at retrieval.